A Study on Semester System at the Undergraduate Level: Activities and Perspectives - Jora, Man Bahadur; Joshi, Bhupesh (Journal of Durgalaxmi, 2025)
This article explores the classroom actions, perspectives, and practices of faculties and aims to reveal the activities that they do. This study, to do this, synthesized the results of qualitative interviews and employed a phenomenological approach. The data in this case were collected from four teachers who were teaching at the bachelor’s level using interview guidelines. The lecture method emerged as the predominant teaching approach, while the semester system was deemed less effective compared to the annual system, and a recurring theme was the lack of adequate resources for students. Aspects like classroom oversight, marking, encouragement, and motivation were not sufficiently met. The education system, while it underwent changes, the shifts that occurred were not sufficiently informed by contemporary changes that the world has witnessed. For the technical programs like Bachelor of Laws and Bachelor of Business Administration, the semester system was more advantageous as it accommodated more contemporary and technical programs.